2021
DOI: 10.1038/s41598-020-79782-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on brain networks during swallowing: general linear model and independent component analyses

Abstract: Swallowing disorders occur more frequently in older adults. However, the effects of the aging process on neural activation when swallowing are unclear. We aimed to identify neural regions activated during swallowing and evaluate changes in neural activation and neural networks with aging. Using a general linear model (GLM) and independent component (IC) analyses, blood oxygen level-dependent (BOLD) signals were observed in the lateral precentral gyrus, postcentral gyrus, anterior insular cortices, supramargina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…However, age was associated with increased brain-activation in the default-mode-network, which is assumed to represent resting-state activation. The authors conclude that aging decreases task-related activation of the swallowing network and reduces task-induced deactivation of the default mode network ( Tae et al, 2021 ). A further fMRI study on 9 healthy older participants (age range 66–77 years) showed reduced activation, especially in somatosensory areas compared to a young control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, age was associated with increased brain-activation in the default-mode-network, which is assumed to represent resting-state activation. The authors conclude that aging decreases task-related activation of the swallowing network and reduces task-induced deactivation of the default mode network ( Tae et al, 2021 ). A further fMRI study on 9 healthy older participants (age range 66–77 years) showed reduced activation, especially in somatosensory areas compared to a young control group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neurostimulation techniques in dysphagia rehabilitation also modulate the cortical swallowing network (Suntrup et al, 2013b(Suntrup et al, , 2015. However, there are only few studies investigating age-related changes in central swallowing control (Martin et al, 2007;Humbert et al, 2009;Malandraki et al, 2010Malandraki et al, , 2011bTeismann et al, 2010;Windel et al, 2015;Tae et al, 2021), with partly inconclusive results: Some studies indicate an increase in cortical activation 10.3389/fnagi.2022.912691 (Martin et al, 2007;Humbert et al, 2009;Teismann et al, 2010), while other studies assume that the swallowing network remains essentially stable regardless of age (Windel et al, 2015) or even decreases in somatosensory areas (Malandraki et al, 2011b;Tae et al, 2021). Common to all of these studies is that neither swallowing function itself nor clinical parameters were related to neuroimaging findings.…”
Section: Introductionmentioning
confidence: 99%
“…This inference may be derived from the action execution function of the SMA proper 66 . But these articles did not segment SMA, or reported activation of SMA proper only, while pre‐SMA has only recently been mentioned as possibly being related to swallowing 14 . In early studies, pre‐SMA was considered to be associated with motor sequences, learning and executive control, which is more like a pre‐frontal area than a motor area.…”
Section: Discussionmentioning
confidence: 99%
“…66 But these articles did not segment SMA, or reported activation of SMA proper only, while pre-SMA has only recently been mentioned as possibly being related to swallowing. 14 In early studies, pre-SMA was considered to be associated with motor sequences, learning and executive control, which is more like a pre-frontal area than a motor area.. 66,68 Some articles suggested that pre-SMA played an important role in controlling voluntary movements by inhibiting or evoking movement. 64,68 Our findings on pre-SMA activation during saliva swallowing supported that advanced motor control is required for saliva swallowing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation